2017
DOI: 10.1080/00224499.2017.1380159
|View full text |Cite
|
Sign up to set email alerts
|

Sexual vs. Nonsexual Currently Most Upsetting Trauma: A Fresh Look at Attenuation of Sexual Response, Alcohol Intoxication, and Post-Traumatic Stress

Abstract: This study examined the dependence of sexual response (vaginal pulse amplitude [VPA] and subjective sexual arousal) on alcohol intoxication (.10% breath alcohol concentration [BrAC] versus no alcohol) and the nature of a woman's currently most upsetting traumatic event (C-MUTE), whether it was sexual (e.g., rape) or nonsexual (e.g., combat). Self-reported sexual outcomes were also compared by C-MUTE type. A total of 117 women completed background measures and either drank alcoholic or nonalcoholic beverages. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 69 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…The decision to focus on women survivors of sexual violence was made based on prior research demonstrating high rates of PTSD in this sample (e.g., Faravelli et al, 2004; Turchik et al, 2012) as well as a dearth of literature in examining the association between PTSS and sexual dysfunctions in women exposed to sexual violence in late adolescence/adulthood. It should be noted that studies that have compared sexual versus nonsexual traumatic events have found higher rates of sexual dysfunction and PTSS in those with a sexual traumatic event (Bird et al, 2018; DiMauro et al, 2018). Thus, it appears that survivors of sexual violence may be particularly vulnerable to both PTSS and sexual dysfunctions, and therefore these findings may be specific to female survivors of sexual violence and may not generalize to other trauma samples or to PTSS’s association with sexual dysfunctions more generally.…”
Section: Discussionmentioning
confidence: 99%
“…The decision to focus on women survivors of sexual violence was made based on prior research demonstrating high rates of PTSD in this sample (e.g., Faravelli et al, 2004; Turchik et al, 2012) as well as a dearth of literature in examining the association between PTSS and sexual dysfunctions in women exposed to sexual violence in late adolescence/adulthood. It should be noted that studies that have compared sexual versus nonsexual traumatic events have found higher rates of sexual dysfunction and PTSS in those with a sexual traumatic event (Bird et al, 2018; DiMauro et al, 2018). Thus, it appears that survivors of sexual violence may be particularly vulnerable to both PTSS and sexual dysfunctions, and therefore these findings may be specific to female survivors of sexual violence and may not generalize to other trauma samples or to PTSS’s association with sexual dysfunctions more generally.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, results from two epidemiological studies observed that a history of sexual violence was associated with poorer sexual function in women (Kadri et al, 2002; Laumann et al, 1999). When sexual traumas were compared to non-sexual traumas, a smaller civilian study observed that those who experienced sexual traumas reported greater sexual dysfunction relative to those who experienced non-sexual traumas (Bird et al, 2018). Preliminary research from a small pilot study conducted in women SM/Vs supports these trends: specifically, sexual traumas were associated with higher distress and lower sexual function relative to non-sexual traumas (DiMauro et al, 2018).…”
mentioning
confidence: 99%